“They attack the family and order”: Right-wing media about feminists and the political consequences of the women's strike in Poland - Żuk, Piotr; Pacześniak, Anna (Frontiers in Sociology, 2023)
The goals of this article are to describe and analyze the main themes in the narratives about feminists that can be found in the populist right-wing press in Poland. Although feminists—alongside LGBT circles, refugees and the left—had been treated as a threat to the existing order before, it was the women's revolt on Polish streets in late autumn 2020 that triggered a series of reports on the women's movement in the right-wing press. In addition to analyzing the content of right-wing weeklies on women's protests, the article also shows how these protests later influenced changes in the political attitudes of young people, social activism and the attitudes of opposition parties in Poland toward cultural and moral issues. The analysis is based on the content analysis of articles published in right-wing weeklies and survey data. The authors conclude that in contemporary Poland the women's movement can contribute to overthrowing not only the rule of the populist right but also the entire conservative order resulting from the post-1989 neoliberal transformation.